Final Design Improvement Of Replica Trophy From Prototype To Mass Production - Tan, Sher Wen (Universiti Sains Malaysia, 2022)
Trophy serves as a recognition and a reminder for a specific achievement. Most of the replica trophy is designed based on the theme of the event. Therefore, reverse engineering is the most suitable way as it transforms real parts into engineering models and is widely used in manufacturing industry. In this paper, it is required to improve the design of the trophy for mass production based on the event of Hall of Fame Universiti Sains Malaysia (Sanggar Sanjung) to celebrate the success of staff. The objectives of this paper are to identify current trend with improvement of functionality and determination of cost saving, time saving and quality improvement in order to produce the final design of replica trophy in mass production. Function analysis and FMEA is conducted to analyze the failure mode effect of the prototype. Few concepts are generated and is further analyzed in the morphology chart. After the concept generation, material and manufacturing process is selected for each part. 3D scanner is used to scan the object (hand) and the data acquisition is obtained by the scanner. The scanned results are discussed to get a better output. The surface finish of 3D printed hand structure is discussed and solved by sanding process. By using the CATIA simulation, suitable toolpath, speed and tool is selected to preview the machining time and output of the part of trophy. This approach can lead to short time consuming as it reduces the error during CNC machining. Then, the selected parts are fabricated by the CNC machine and 3D printing respectively. The cost for fabricating a single trophy and mass production is compared and it can be concluded that mass production of trophy can reduce the costing with RM93.86 whereas single production is RM187.54. Lastly The time taken for single trophy is 12.20 hours and 10 trophies is 11dayswhich is simulated by Witness Horizon software.